INTERPERSONAL COMMUNICATION OF LECTURERS IN SHAPING THE STUDENT’S CHARACTER OF STAIN MANDAILING NATAL - Marlina (KOMUNIKE: Jurnal Komunikasi Penyiaran Islam, 2022)
Students are a social group that acts as an agent of change in the midst of society and should have a positive character, in terms of thinking and behavior. This research was conducted on STAIN Mandailing Natal students in 2021 by taking 40 students. This research uses qualitative methods with interview and observation techniques, using interpersonal communication theory. The results of this study are first; Interpersonal communication carried out by lecturers who follow the student's style will get positive acceptance.  Secondly; students who communicate formally and seem to have a distance between lecturers and students tend to be ignorant in carrying out academic activities.